Expression pattern of estrogen, progesterone and HER2/neu receptors in atypical breast lesions does not predict subsequent clinically significant event - Tjoe, Judy A; Neitzl, Gary F; Singh, Maharaj; Last, Brittany S; Kansra, Sanjay (Advocate Aurora Health Institutional Repository, 2014)
Background: While 5-year survival rates for breast cancer patients have improved, we still cannot predict whether early breast lesions, such as atypical ductal hyperplasia (ADH) or atypical lobular hyperplasia (ALH), are harbingers of future cancer. Atypia increases the risk of developing subsequent breast cancer four- to fivefold. To avoid this, women may opt for aggressive management with associated side effects. Thus, identifying predictors of future breast cancer after a diagnosis of atypia would assist in risk reduction strategy selection. Purpose: Given that lifetime estrogen exposure is a significant risk factor for breast cancer, and human epidermal growth factor receptor-2 (HER2/neu) gene amplification is linked to cancer pathogenesis, we tested whether expression patterns of estrogen receptor (ER), progesterone receptor (PR) and HER2/neu at initial diagnosis of atypia predicted a subsequent clinically significant event (SCSE), i.e. another occurrence of atypia, in situ or invasive carcinoma. Methods: Patients with an initial diagnosis of ADH and/ or ALH were retrospectively identified. A study cohort of 19 women who developed SCSE (cases) was matched to 45 women with no SCSE for at least 5 years after atypia diagnosis (controls). Archived tissues from cases and controls were subjected to immunohistochemical analysis of ER, PR and HER2/neu. ER and PR staining patterns were reported using Allred score, while HER2/neu expression was reported as negative (0-1+), equivocal (2+) or positive (3+). Atypia with HER2/neu 2+ or 3+ scores were subject to FISH analysis to confirm gene amplification. Results: There was no significant difference in expression of ER (mean Allred score: cases = 7.26 ± 0.35; controls = 6.91 ± 0.43) or PR (mean Allred score: cases = 6.95 ± 0.43; controls = 6.57 ± 0.34). Greater than 90% of both cases and controls were negative (0-1+) for expression of HER2/neu. Longitudinal assessment of ER, PR and HER2/neu expression in the cohort of patients who developed SCSE revealed that 3 of the 19 ...